Contemporary migration crisis in Europe and its consequences (International relations and international law Journal, 2016)
European countries take actions to overcome the influx of refugees. Governments of EU face with a range of difficulties and risks. In this research analyzes contemporary situation with refugees in EU, describe consequences of crisis, measures and approaches to solve this problem. The importance of migration in the socio-economic and political processes on the example of the European Union is considered on this article. The subject of the research is the immigration policy of the European Union in new geopolitical environment, especially in the circumstances of Syrian crisis. Nowadays EU is the centre of attraction for lots of refugees. To control illegal migration streams, EU uses different migration policy instruments targeted towards short and middle-range objectives and development policy oriented on addressing root causes of migration from developing countries.
Keywords: refugees; Europe; crisis; European Union; migration